Difference between revisions of "009A Sample Final A, Problem 4"
Jump to navigation
Jump to search
(Created page with "<br> <span style="font-size:135%"><font face=Times Roman> 4. Find an equation for the tangent line to the function <math style="vertical-align: -13%;">-x^{3}-2xy+y^{3}=-...") |
m |
||
Line 17: | Line 17: | ||
|- | |- | ||
| <math>2\cdot y+2x\cdot y' = 2y +2x\cdot y'.</math> | | <math>2\cdot y+2x\cdot y' = 2y +2x\cdot y'.</math> | ||
+ | |- | ||
+ | |<br> | ||
|} | |} | ||
Line 24: | Line 26: | ||
|We use implicit differentiation on our original equation to find | |We use implicit differentiation on our original equation to find | ||
|- | |- | ||
− | | | + | | <math>-3x^{2}-2y-2x\cdot y'+3y^{2}\cdot y'=0.</math> |
|- | |- | ||
− | | | + | |From here, I would immediately plug in (1,1) to find ''y'' ': |
|- | |- | ||
− | | | + | | <math style="vertical-align: -20%">-3-2-2y'+3y'=0</math>, or <math style="vertical-align: -20%">y' = 5.</math> |
+ | |- | ||
+ | |<br> | ||
|} | |} | ||
Line 34: | Line 38: | ||
!Writing the Equation of the Tangent Line: | !Writing the Equation of the Tangent Line: | ||
|- | |- | ||
− | |Now, we simply plug our values of ''x'' = ''y'' = 1 and ''m'' = 5 into the point-slope form to find the tangent line through (1,1) is <math | + | |Now, we simply plug our values of ''x'' = ''y'' = 1 and ''m'' = 5 into the point-slope form to find the tangent line through (1,1) is |
+ | |- | ||
+ | | <math>y-1=5(x-1),</math> | ||
+ | |- | ||
+ | |or in slope-intercept form | ||
+ | |- | ||
+ | | <math>y=5x-4.</math> | ||
+ | |- | ||
+ | |<br> | ||
|} | |} | ||
[[009A_Sample_Final_A|'''<u>Return to Sample Exam</u>''']] | [[009A_Sample_Final_A|'''<u>Return to Sample Exam</u>''']] |
Revision as of 10:19, 25 March 2015
4. Find an equation for the tangent
line to the function at the point .
Foundations: |
---|
Since only two variables are present, we are going to differentiate everything with respect to x in order to find an expression for the slope, m = y ' = dy/dx. Then we can use the point-slope equation form at the point to find the equation of the tangent line. |
Note that implicit differentiation will require the product rule and the chain rule. In particular, differentiating 2xy must be treated as |
which has as a derivative |
Finding the slope: |
---|
We use implicit differentiation on our original equation to find |
From here, I would immediately plug in (1,1) to find y ': |
, or |
Writing the Equation of the Tangent Line: |
---|
Now, we simply plug our values of x = y = 1 and m = 5 into the point-slope form to find the tangent line through (1,1) is |
or in slope-intercept form |